Oxidant-Antioxidant System of Oral Fluid in Patients with Generalized Pаrodontal Diseases Associated with Eating Disorders - Reshetnyk Л. Л.; Popov Р. В. (Actual Dentistry, 2025)
Actuality. The main reason for the failure of specific and nonspecific body protection mechanisms in many diseases and pathological conditions is an imbalance in the prooxidant-antioxidant system. A significant imbalance in it is accompanied by the development of oxidative stress with its pathological components. The presence of oxidative stress is noted in a number of physiological and pathological conditions. Chronic obstructive pulmonary disease of occupational etiology, a disease common among mining workers, is no exception. Aim: compare the oral cavity’s health status and saliva’s antioxidant system in patients with generalized periodontal diseases in anorexia nervosa and healthy people from the control group. Material and methods. The study included 25 women with anorexia nervosa and 25 healthy controls. Clinical indicators and saliva samples were collected from each patient. Superoxide dismutase activity was assessed. Results. The concentration of SOD in saliva was significantly higher in patients with AN with GPD compared to the control group (1.010 ± 0.46 vs. 0.579 ± 0.296 U/ml; p = 0.0003). No significant differences were found between the groups in hROS (233.72 ± 88.3 vs. 199.49 ± 74.72; p = 0.15). Although most patients recognize the importance of oral hygiene for maintaining good oral health, more than half of them have poor oral hygiene. Conclusions. The altered biochemical composition of saliva in patients with GPD and AN can be interpreted as an effective mechanism of protection against oxidative stress. Moreover, despite the discrepancy between clinical data and perceptions of oral health in the population of patients with AN, the quality of life of these patients does not seem to be significantly affected by the condition of their teeth.